The Effect of Savings Shuttle Service Quality and Complaint Handling on Member Loyalty at BMT NU Muncar Branch - Nuraini, Septia; Khusnudin, Imam (Universitas Islam Negeri Alauddin Makassar, 2025)
Aims to determine the effect of the quality of savings pick-up and delivery services and complaint handling on member loyalty at KSPPS BMT NU Muncar, a sharia microfinance institution. As an LKM (Microfinance Institution), BMT aims to serve people who have not been reached by conventional banking, provide financing for micro businesses, facilitate savings, and avoid usury practices. BMT NU Muncar in its operations focuses on increasing member trust and satisfaction as an effort to build loyalty. This study uses a quantitative method with a descriptive approach, involving 67 samples from 200 active members who use savings pick-up and delivery services. The sample was determined by purposive sampling technique using the Slovin formula with primary data collected through a questionnaire measured using a 4-point Likert scale. Data analysis was conducted using SPSS version 23, which includes statistical tests such as the Determination Coefficient Test, F Test, and T Test. The results of the study showed that the F test results showed that the calculated F value was 201.682, while the F table value was 2.3516584, with a significance level (p-value) of 0.000 which was smaller than 0.05 (0.000 ≤ 0.05). The R-Square test results showed a value of 0.863 or 86.3%, which means that 86.3% of the variation in member satisfaction was influenced by the independent variables (Quality of Shuttle Services and Complaint Handling), while the remaining 13.7% was influenced by other factors. This study is expected to provide insight for BMT NU Muncar in increasing competitiveness and operational sustainability by increasing member loyalty. The implications of the study suggest that it is important for BMT to continue to adapt to member needs and ensure operational sustainability through improving service quality that can increase satisfaction levels and ultimately strengthen member loyalty.